Fractographic study on the competitive bending fracture mechanisms of High-Nb TiAl alloys - Lin, Youzhi; Liao, Ping; Liu, Bingzhi (Frontiers in Materials, 2026)
To address the challenges of limited room-temperature ductility and low damage tolerance in high-Nb TiAl alloys and to improve their overall mechanical performance, this study investigates their fracture mechanism and intrinsic brittleness through bending tests combined with detailed fractographic analysis. Through bending and unloading experiments combined with scanning electron microscopy (SEM) observations of fracture surfaces and specimen morphologies, the results revealed that cracks initiated abruptly and led to catastrophic fracture once the applied bending load reached a critical level. In addition to the main crack initiation source, one or two secondary initiation sites were also identified on the fracture surfaces of the unloaded specimens. Variations in the crack lengths observed under different external unloading stresses indicate differences in the location and size of the cleavage initiation zone, rather than implying a progressive crack initiation–coalescence–fracture process. The borides within the alloy acted as dislocation obstacles or ligament bridges, effectively impeding further microcrack propagation or altering crack paths. These mechanisms enhanced the alloy’s resistance to crack initiation and propagation, thereby improving its fracture toughness. The fracture process can be summarized as follows: when the grains at the notch root are favorably oriented, cracks initiate within these grains and propagate along favorable colony boundaries or interlamellar interfaces, releasing stored strain energy and triggering cleavage across the entire specimen. In contrast, when the notch-root grains are unfavorably oriented, strain energy accumulates near the crack tip until a critical threshold is reached, resulting in instantaneous brittle cleavage fracture.